2015
DOI: 10.3390/ijerph121215032
|View full text |Cite
|
Sign up to set email alerts
|

Reading Books and Watching Films as a Protective Factor against Suicidal Ideation

Abstract: Reading books and watching films were investigated as protective factors for serious suicidal ideation (SSI) in young people with low perceived social belonging. Cross-sectional and longitudinal (12-month) analyses were performed using data from a representative European sample of 3256 students from the “Saving and Empowering Young Lives in Europe” study. Low social belonging was associated to SSI. However, reading books and watching films moderated this association, especially for those with lowest levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In addition to the protective factors that have been mentioned, reading books and watching films is also one of the protective factors of suicide behavior in adolescents. The more the number of books reads and films watched, the lower the risk of suicide ideation in adolescents (Kasahara‐Kiritani et al, 2015). The last factor identified as a protective factor for suicidal behavior in adolescents is faith or religiosity.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the protective factors that have been mentioned, reading books and watching films is also one of the protective factors of suicide behavior in adolescents. The more the number of books reads and films watched, the lower the risk of suicide ideation in adolescents (Kasahara‐Kiritani et al, 2015). The last factor identified as a protective factor for suicidal behavior in adolescents is faith or religiosity.…”
Section: Resultsmentioning
confidence: 99%
“…A controlled study showed that acceptance and commitment therapy reduces suicidal ideation and psychological pain in high-risk patients with depression [ 107 ] and seems to have anti-inflammatory effects [ 130 ]. Engagement in art provides some forms of social support to isolated people and may increase the sense of belonging as well as protect from suicidal ideation [ 131 ]. In parallel to social connection, art also reduces cytokine levels in serum, such as IL-6 [ 132 ].…”
Section: Introductionmentioning
confidence: 99%
“…They facilitate dialogue, reduce stigma, and enhance expression, coping skills, empathy, and personal and cultural resonance, all of which address risk factors for suicide (Fancourt et al, 2019; Michalak et al, 2014; Sonke et al, 2020). They can also facilitate expression of emotions like entrapment, loneliness, and burdensomeness (Aguilar, 2017), cultivate belonging (Perkins et al, 2016), and protect against suicidal ideation (Kasahara-Kiritani et al, 2015). However, evidence regarding how the arts can support suicide prevention and survivorship is limited.…”
mentioning
confidence: 99%